The impact of wildfire on microbial C:N:P stoichiometry and the fungal-to-bacterial ratio in permafrost soil - Zhou, Xuan; Sun, Hui; Pumpanen, Jukka; Sietiö, Outi-Maaria; Heinonsalo, Jussi; Köster, Kajar; Berninger, Frank (Biogeochemistry, 2019)
Wildfires thaw near-surface permafrost soils in the boreal forest, making previously frozen organic matter available to microbes. The short-term microbial stoichiometric dynamics following a wildfire are critical to understanding the soil element variations in thawing permafrost. Thus, we selected a boreal wildfire chronosequence in a region of continuous permafrost, where the last wildfire occurred 3, 25, 46, and > 100 years ago (set as the control) to explore the impact of wildfire on the soil chemistry, soil microbial stoichiometry, and the fungal-to-bacterial gene ratio (F:B ratio). We observed the microbial biomass C:N:P ratio remained constant in distinct age classes indicating that microbes are homeostatic in relation to stoichiometric ratios. The microbial C:N ratios were independent of the shifts in the fungal-to-bacterial ratio when C:N exceeded 12. Wildfire-induced reduction in vegetation biomass positively affected the fungal, but not the bacterial, gene copy number. The decline in microbial biomass C, N, and P following a fire, primarily resulted from a lack of soil available C and nutrients. Wildfire affected neither the microbial biomass nor the F:B ratios at a soil depth of 30 cm. We conclude that microbial stoichiometry does not always respond to changes in the fungal-to-bacterial ratio and that wildfire-induced permafrost thawing does not accelerate microbial respiration. Peer reviewed